Estudo, projeto e implementação de um modelador de sólidos voltado para aplicação em eletromagnetismo - Ana Liddy Cenni de Castro Magalhaes (2000)
This work covers the development of a solid modeler based on advanced techniques of tridimensional geometric modeling. It will be coupled to an adaptive mesh generator of a pre-processor, aiming at the solution of electromagnetic problems by means of finite-element method. Manufacturable models can be obtained through the combination of CSG (Constructive Solid Geometry) primitives directly instantiated or defined by sweep operations. The boundary (B-rep) representation as well as the finiteelement surface mesh are derived from the CSG model. A new B-rep data structure represents the modeler main innovation, since it allows the handling of inner boundaries between the components of manufacturable B-rep models, guarantying the uniqueness of the inner boundary representation and assuring the finite-element compatibility forthe generated mesh. This modeler also generates complex primitives by sweeping or swinging multi-contour profiles, which reduces the necessity for boolean operations. Besides supporting and speeding up the processes of creation, manipulation and visualization of manufacturable solid representations, the main goal of this modeler is to generate a good surface finite-element mesh, capable of providing the essentialinformation for the electromagnetic simulation of the model. The modeler is composed of four main subsystems: the Interface, responsible for the user access on model creation, edition and visualization; the Modeling subsystem, enclosing the operations for shape manipulation; the Kernel, which manages and controls data structures access; the Mesh Generation subsystem, responsible for the creation and improvements of surface finite-element meshes. The modeler is being developed by the GOPAC Optimization and Computer-Aided Design Group at CPDEE / UFMG Center of Research and Development on Electrical Engineering / Federal University of Minas Gerais. It uses object-oriented concepts, the Borland C++ Builder environment coupled to the OpenGL graphics library and the STL Standard Template Library. The results obtained can bestored in a neutral format database, which will allow information interchange with other applications and assure the modeler potential for engineering applications.